Does kinesiophobia affect the early functional outcomes following total knee arthroplasty? - Guney-Deniz, Hande; Kinikli, Gizem Irem; Caglar, Omuer; Atilla, Bulent; Yuksel, Inci (Taylor & Francis Inc, 2017)
The purpose of this study was to investigate the effects of kinesiophobia on early functional outcomes in patients following total knee arthroplasty (TKA) and how kinesiophobia is related to functional outcomes and pain. The Tampa Scale for Kinesiophobia (TSK), 2-minute walk test (2-MWT), and the timed up and go test (TUG) were used to assess 46 TKA patients on discharge day. The pain levels and active knee flexion range of motion (ROM) were recorded. Patients were divided into two groups as high kinesiophobia (Group I, n=22) and low kinesiophobia (Group II, n=24) based on the TSK levels. The TUG results were similar between groups (p=0.826). 2-MWT results (p<0.001), pain levels (p=0.003), and knee flexion ROM (p=0.025) scores were better in Group II when compared to Group I. The TSK scores were significantly correlated with 2-MWT results (r=-0.40; p=0.003), pain levels (r=0.80; p<0.001), and knee flexion ROM (r=-0.47; p=0.001). The regression analysis revealed that 41% of 2-MWT score, 47% of knee flexion ROM, and 60% of pain level changes could be explained by kinesiophobia level. The results suggest that early outcomes following TKA were affected by the pain-related fear of movement. The clinicians need to consider the interrelationships between fear of movement and functional outcomes when designing, implementing, and monitoring daily therapeutic exercise programs.
Keywords: Fear of movement; functional outcomes; kinesiophobia; pain; total knee arthroplasty